Категорія чудесного в полемічній прозі (чудесне у "Пересторозі") - Дубініна, К. (Літературознавчі обрії. Праці молодих учених, 2010)
In the article the meaning of concepts of «the wonderful» and «the miraculous», their origin and functioning from the point of medieval imagination and Christian world view are exposed. An attempt to explain for what purpose polemicists used the element of the wonderful in their rhetoric is made. Three directions in which «the category of the wonderful» was developing are considered: symbolic, instructive and rhetorical.